The Practice of Qur'anic and Tafsir Integration in Thesis Writing: Challenges and Patterns at Biology Education Department UIN Alauddin Makassar - Emir Surya Kautsar; Sohrah; Umni Alwiyah; Asniati Jabbar (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2025)
ntegrating Islamic science and natural science is a significant challenge in Islamic higher education in Indonesia. This research aims to analyse the implementation of this integration in thesis writing and its impact on the development of Islam-based science at Alauddin State Islamic University Makassar. This qualitative study, which includes data quantification, combines field research and literature review frameworks with a case study approach. Data were collected through thesis document analysis, supported by interviews and questionnaires. Content analysis was used to evaluate the extent to which verses of the Qur'an and their interpretations are integrated with biological studies in a relevant and scientific manner. The results indicate that the majority of students' theses incorporate the Qur'an and its exegesis as a theological foundation, particularly in topics such as ecology, environmental preservation, and biodiversity. However, the implementation of this integration faces several challenges, including a lack of tafsir literature relevant to biological themes and limited student understanding of scientific interpretation methods. Despite these challenges, the integration positively impacts students by strengthening their spiritual values and fostering Islamic-based ecological awareness. The implications of this research highlight the need for developing more systematic scientific integration modules, providing training in scientific interpretation methods for lecturers and students, and strengthening collaboration between science (Biology) and interpretation. These efforts aim to produce integrated scientific works that are academically relevant and contribute to society.